2013
DOI: 10.1016/j.pep.2013.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Bacterially expressed human serotonin receptor 3A is functionally reconstituted in proteoliposomes

Abstract: Human serotonin receptor 3A (5-HT3A) is a ligand-gated ion channel regulated by serotonin. A fusion protein (P9-5-HT3A) of 5-HT3A with the P9 protein, a major envelope protein of bacteriophage phi6, was highly expressed in the membrane fraction of Escherichia coli, and the expressed protein was purified to homogeneity using an affinity chromatography. P9-5-HT3A was observed as mixed oligomers in detergents. The purified P9-5-HT3A was efficiently reconstituted into proteoliposomes, and the serotonin-dependent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The in vivo and in vitro dsRNA replication systems based on phi6 polymerase complex or RNA-dependent RNA polymerase enable the large-scale production of high-quality dsRNA molecules [81,128] to be used in RNA interference applications against plant and human pathogens [81,129,130,131,132,133] or to induce innate immunity responses in human cell lines [134]. In addition, the phi6 major membrane protein has been used to improve the correct folding of heterologous membrane proteins in bacterial expression systems [135,136] and to produce phi6-specific synthetic lipid scaffolds for enzymatic reactions in E. coli [137].…”
Section: Applications Of Membrane-containing Phagesmentioning
confidence: 99%
“…The in vivo and in vitro dsRNA replication systems based on phi6 polymerase complex or RNA-dependent RNA polymerase enable the large-scale production of high-quality dsRNA molecules [81,128] to be used in RNA interference applications against plant and human pathogens [81,129,130,131,132,133] or to induce innate immunity responses in human cell lines [134]. In addition, the phi6 major membrane protein has been used to improve the correct folding of heterologous membrane proteins in bacterial expression systems [135,136] and to produce phi6-specific synthetic lipid scaffolds for enzymatic reactions in E. coli [137].…”
Section: Applications Of Membrane-containing Phagesmentioning
confidence: 99%
“…In fact, we showed recently that HTR3A expressed by pMP6 is functional in the binding of its ligand [27].…”
Section: Expression Of Membrane Proteins As P9 Fusionsmentioning
confidence: 99%
“…Previously, we have shown that membrane proteins can be highly expressed in the membrane fraction of E . coli as fusion proteins of the P9 envelope protein of bacteriophage phi6 . An expression vector of LPA 1 was constructed as a fusion protein of P9 in which the coding sequence of LPA 1 was fused at the C‐terminus of P9, which was flanked by protease cleavage sites and His‐tag sequences at the N‐ and C‐terminus of LPA 1 , respectively (Figure (a)).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we developed an efficient expression system for membrane proteins, including GPCRs in Escherichia coli , in which a short single transmembrane envelope protein, P9, of Pseudomonas phage phi6 is fused at the N‐terminus of the target membrane protein . With this expression system, milligram quantities of GPCR, such as human endotheline receptor (ET A ) or ligand‐gated ion channel, e.g ., serotonin receptor type 5, can be easily prepared at a liter culture scale.…”
Section: Introductionmentioning
confidence: 99%